Unhealthy Food Consumption Is Associated with Post-Acute Sequelae of COVID-19 in Brazilian Elderly People - Guilherme José Silva Ribeiro; Rafaela Nogueira Gomes de Morais; Olufemi Gabriel Abimbola; Nalva de Paula Dias; Mariana De Santis Filgueiras; André de Araújo Pinto; Juliana Farias de Novaes (Infectious Disease Reports)
Background/Objectives: The factors associated with post-acute sequelae of COVID-19 (PASC) are not yet fully understood in developing countries. Our objective was to investigate the relationship between food consumption and the occurrence of PASC in Brazilian elderly people. Methods: This cross-sectional study included 1322 elderly people aged 60 or over, infected with SARS-CoV-2 in 2020, living in the state of Roraima in Brazil. Using the Brazilian National Food and Nutrition Surveillance System (SISVAN, in Portuguese) tool, food consumption markers were evaluated. The persistence of post-acute sequelae of COVID-19 was assessed three months after SARS-CoV-2 infection. Poisson regression with robust variance was performed to estimate the prevalence ratio (PR) with a 95% confidence interval (95% CI). Results: Fruit consumption [PR 0.92; 95% CI: 0.85–0.99] was associated with a lower occurrence of PASC, with a significant interaction in individuals aged 60 to 69 years old, not hospitalized, and those without chronic kidney disease. In addition, the consumption of sugar-sweetened beverages [PR 1.23; 95% CI: 1.12–1.35], sandwich cookies, sweets, and treats [PR 1.12; 95% CI 1.03–1.22] was positively associated with the occurrence of PASC in the elderly people, with a significant interaction in individuals living in the capital and without hypercholesterolemia. Conclusions: Unhealthy food consumption was associated with PASC in Brazilian elderly people. An improvement in the diet quality of elderly people is necessary to minimize health complications in PASC.